"Il tramonto d'Europa". Ungaretti e le poetiche del secondo Novecento - Manghetti, Gloria; Caporiccio, Elisa; Spignoli, Teresa; LO MONACO, GIOVANNA (Biblioteca di Studi di Filologia Moderna, 2023)
The shift between the first and second half of the twentieth century marked a watershed. It represented the "sunset of modernity" and made tradition unattainable, thereby calling into question the very survival of poetry. This collection focuses on the work of Giuseppe Ungaretti as poet, translator, and critic, which took the lead from this fracture. As the essays gathered here show, this fracture took a specific shape in Ungaretti's work, which was reviewed in distinct ways and had a lasting impact up to the present day, alongside twentieth-century history and poetry. The book thus offers a multifaceted picture aimed at assessing albeit provisionally the later Ungaretti's writings and his legacy for future generations of writers.